Institutional environment, ownership and firm taxation. Issue 1 (26th November 2012) - Wu, Wenfeng; Rui, Oliver M.; Wu, Chongfeng
Abstract This paper examines how ownership type and institutional environment affect firm taxation. Using a sample of Chinese‐listed firms from 1999 to 2006, we find that private firms enjoy a lower effective tax rate than local state‐owned enterprises. In addition, the preferential taxation of private firms is associated with local government incentives to promote local economic growth. We find that private firms located in regions with a lower level of privatization receive preferential tax treatment. Our results also suggest that decentralization and interjurisdictional competition lead to financial interdependence between local governments and private firms.